(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The study aimed to explore the role of faculty members at Qassim University in digital volunteering in light of Saudi Arabia’s Vision 2030, as well as to identify the obstacles they face and ways to enhance their role in this field. The researcher employed the descriptive survey method and developed a questionnaire consisting of 45 statements, which was administered to a simple random sample of 271 faculty members. The results indicated that the role of faculty members at Qassim University in digital volunteering was achieved to a moderate degree, with a mean score of (2.70). The obstacles they face were found to be at a high level, with a mean score of (3.57). The main obstacles were the faculty members’ involvement in research and teaching duties, which reduce opportunities for digital volunteering, the difficulty in allocating sufficient time for digital volunteer work, and the lack of media campaigns supporting digital volunteering activities. Furthermore, the participants agreed to a high degree on the ways to enhance the role of faculty members in digital volunteering, with a mean score of (3.99). The most significant enhancement strategies included the university establishing partnerships with community institutions to provide digital volunteer projects that align with faculty members’ specializations, offering specialized training courses on digital volunteering as part of faculty professional development programs, and providing a range of digital volunteer projects suited to the university environment.